PERBEDAAN JARAK TANAM TERHADAP PRODUKTIVITAS RATOON RUMPUT GAJAH (Pennisetum purpureum Cv. Mott) - Dewi Lestari; Nita opi ari kustanti; Edya Moelia Moeis (Universitas Islam Balitar, 2018)
This study was to determine the effect of plant spacing on ratoon productivity elephant grass (Pennisetum purpureum Cv. Mott). The experiment method was conducted experimentally by experiment with diffent spacing on Ratoon Elephant Grass (Pennisetum purpureum Cv. Mott).The desigh used was a complete randomized design (RAL) with 4 treatments and 6 replications, ie P0 (50 x 100) cm, P1 (75 x 100) cm, P2 (100 x 100) cm and P3 ( 125 x 100) cm. From result showed that P0 (50 x 100) cm yielded the highest number of tillers, which was 15.78 piece and followed by P1 (75 x100) cm yielding plant height of 86.37 cm, P2 (100 x 100) cm of 679.11 gr in fresh weight and P3 (125 x 100) cm of 156.96 piece on the number of leaves. According to the results of the study can be concluded that the spacing is not significant (P>0.05) on Ratoon Elephant Grass. Need further research on the influence of devoliation, weed control and high influence of low area of Raton Elephat Grass (Pennisetum purpureum Cv. Mott).